Barriers and drivers for energy efficiency: Different perspectives from an exploratory study in the Netherlands. (15th September 2015) - Cagno, Enrico; Trianni, Andrea; Abeelen, Christiaan; Worrell, Ernst; Miggiano, Federica
Highlights: We investigated the perception of barriers and drivers and mechanisms regulating them. Firms agree on the most important barriers and drivers. Firms agree on the most critical decision-making steps and actors promoting drivers. Major external actors perceive barriers, drivers and mechanisms differently. Success of voluntary agreements depends on the link to other policy instruments. Abstract: Increased energy efficiency represents a crucial opportunity for European industrial sustainability, but several barriers still need to be tackled. Thus, it is crucial to understand the existing mismatches between the perception of enterprises and what the major actors promoting energy efficiency believe enterprises suffer from and need within the decision-making process. To do so, we have performed an exploratory investigation analysing a set of manufacturing enterprises participating in the Dutch voluntary agreements. The study involved the major external actors, i.e. the national energy agency, governmental and industrial organisations, to map their views on the decision-making process. Results show that enterprises agree not only on the most important barriers and drivers, but also on the mechanisms underlying them. However, even a general common understanding of the barriers is disputed when major external actors are considered, as they only agree on the primary role of economic barriers. Mismatches appear when considering how single barriers affect the decision-making process and which drivers – and actors promoting them – need to be addressed. Although voluntary agreements represent the most popular instrument on energy efficiency in the Netherlands, they do not seem to be considered by small and medium-sized enterprises as a stimulus for improving energy efficiency. Crucial for future success are the link with other policy instruments, and the degree to which the instruments trigger the right drivers and barriers at the right moment.